The Impact of Organizational Justice on Turnover Intention Among Primary Healthcare Workers: The Mediating Role of Work Motivation - Zhao S; Ma Z; Li H; Wang Z; Wang Y; Ma H (Risk Management and Healthcare Policy)
Shichao Zhao,1 Zhaofei Ma,1 Hongyu Li,1 Zhanning Wang,1 Ying Wang,2,* Huifen Ma3,* 1School of Public Administration, Shandong Normal University, Jinan, Shandong, People’s Republic of China; 2School of Health Management, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People’s Republic of China; 3School of Medical Management, Shandong First Medical University, Jinan, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ying Wang, School of Health Management, Shandong University of Traditional Chinese Medicine, No. 4655 University Road, Jinan, Shandong, 250355, People’s Republic of China, Tel/Fax +0086-13869161627, Email yingwang_2016@163.com Huifen Ma, School of Medical Management, Shandong First Medical University, No. 6699 Qingdao Road, Jinan, Shandong, 250117, People’s Republic of China, Tel/Fax +0086-15600684995, Email hfma@sdfmu.edu.cnBackground: Adequate staffing of primary healthcare workers (PHCWs) is essential for strengthening healthcare systems, yet high turnover intention among these workers presents a significant challenge. While existing strategies primarily target economic incentives and career progression, this study proposes that enhancing organizational justice could offer a novel and impactful approach to retention. Drawing on equity theory and self-determination theory, the study examines how organizational justice influences turnover intention and the mediating roles of both the intensity and type of work motivation.Methods: This is a cross-sectional study design. A multi-stage cluster sampling method was utilized to administer a questionnaire survey to 1,200 PHCWs from 36 primary health institutions in Shandong Province, China.Results: Multivariate linear regression analysis revealed that organizational justice significantly reduces turnover intention among PHCWs (β = − 0.435, p < 0.001). Among its three dimensions, distributive justice (β = − 0.203, p < 0.001) and procedural justice (β = − 0.177, p < 0.01) had significant impacts on turnover intention, whereas interactional justice did not. The study also confirmed the mediating role of work motivation, with work motivation type accounting for 18.2% of the total effect, exerting a greater influence than work motivation intensity, which accounted for 13.8% of the total effect.Conclusion: This study finds that organizational justice, especially distributive and procedural justice, reduces turnover intention among PHCWs in China. Work motivation mediates this effect, with motivation type having a stronger influence than motivation intensity. Enhancing organizational justice through transparent systems for compensation, promotion, and inclusive decision-making can foster the internalization of work motivation, providing a sustainable approach to improving retention and supporting the stability of the primary healthcare workforce.Keywords: organizational justice, turnover intention, work motivation, primary healthcare worker